PENGGUNAAN METODE AUDIO VISUAL DAN MEDIA PEMBELAJARAN MICROSOFT POWER POINT TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 86 KOTA BENGKULU - Septi Yuliza (IAIN Bengkulu, 2018)
This research is to know whether there is influence from using audiovisual method and microsoft power point learn- ing media to motivation of student learning on Islamic Education subject in SD Negeri 86 Kota Bengkulu.This research uses quantitative approach. The population is all elementary school students 86 Bengkulu City. sampling is done by purposive sampling that is determination technique with certain consideration. Data were analyzed using simple linear re- gression test. The results showed that the variable of audiovisual method (X1) and microsoft power point (X2) had a positive effect on students’ learning motivation State primary school 86 Bengkulu city. In the test, it can be seen that the influence of visual audio method variable (X1) on student learning motivation (Y) is 9,3%, while the rest 90,7% influenced by other than variable X1. Variable of learning media of Microsoft Power Point (X2) can influence Student Motivation Motivation variable equal to 34,5%, while the rest of 65,5% influenced by other variable besides variable of learning media Microsoft power point. Together, the variables of audio visual method and learning media of Microsoft power point can influence student’s learning motivation equal to 34,6%, while the rest of 65,4% influenced by other variable beside variable of audio visual method and Microsoft Power Point learning media